2019
DOI: 10.1371/journal.pone.0217571
|View full text |Cite
|
Sign up to set email alerts
|

Maize responsiveness to Azospirillum brasilense: Insights into genetic control, heterosis and genomic prediction

Abstract: Several studies have shown differences in the abilities of maize genotypes to facilitate or impede Azospirillum brasilense colonization and to receive benefits from this association. Hence, our aim was to study the genetic control, heterosis effect and the prediction accuracy of the shoot and root traits of maize in response to A . brasilense . For that, we evaluated 118 hybrids under two contrasting scenarios: i) N str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 68 publications
(77 reference statements)
3
20
1
Order By: Relevance
“…Even though sugars are reported as the main class of root-released compounds by plants [ 13 , 14 ], in the present study, this trend has not been confirmed, as our root exudates contained 60% of amino acids, followed by 30% sugars and 10% organic acids. This contrasting result may be related to the high rates of amino acids released by plant roots at early growth stages, as we sampled the plants at seedling stages [ 15 ].…”
Section: Discussioncontrasting
confidence: 85%
See 2 more Smart Citations
“…Even though sugars are reported as the main class of root-released compounds by plants [ 13 , 14 ], in the present study, this trend has not been confirmed, as our root exudates contained 60% of amino acids, followed by 30% sugars and 10% organic acids. This contrasting result may be related to the high rates of amino acids released by plant roots at early growth stages, as we sampled the plants at seedling stages [ 15 ].…”
Section: Discussioncontrasting
confidence: 85%
“…Therefore, further researches on the role of root exudates as mediators of the corn- Azospirillum symbiosis need to be carried out, including regarding the amino acids classes, as despite their null chemotaxis, they seemed to be determinant in the degree of the benefits provided by A. brasilense. Additionally, rather than being the cause of the responsiveness, root exudates are more likely to reflect the specificity of transcriptional signaling involved in the mutual recognitions between Azospirillum and its host plant [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the GP of the hybrid's performance, we used a two-stage approach [13], where, in the first stage, the phenotypes were corrected for the experimental design effects, and in the second stage, the prediction models were fitted using the adjusted phenotypes. The details of the model and steps in implementation are explained in our earlier study [51]. In brief, this method is based on the commonly used additive effect model.…”
Section: Genomic Predictionmentioning
confidence: 99%
“…The larger proportion of the mean squares of the GCA compared to SCA for HMF and HF suggests that the additive genetic effect was the main contributor to their inheritance in the F1 hybrids in the two evaluated environments. In a diallel experiment with a fixed-effects model, even though the estimates of additive and dominance variances are less important [ 26 ], the GCA–SCA ratio (GSR) proposed by Baker [ 27 ] (Baker’s ratio) is frequently used in several studies [ 28 , 29 , 30 ] to determine the relative importance of GCA and SCA. If the Baker’s ratio is close to 1, then GCA is predominant for a given trait.…”
Section: Discussionmentioning
confidence: 99%